Muyocoxanthones O–S: Undescribed xanthones with antioxidative damage bioactivity to cardiomyocytes from the endophytic fungus Muyocopron laterale. (May 2023) - Cao, Hai-Yan; Sun, Sen-feng; Yi, Cheng; Yang, Chen-yu; Chen, Ke-liang; Zhang, Xiao-wei; Liu, Yun-Bao
Abstract: The metabolites from the endophytic fungus Muyocopron laterale hosted in the medicinal plant Tylophora ovata were investigated, and five undescribed xanthones, muyocoxanthones O–S, along with seven known compounds were isolated. Their structures were elucidated by HR-ESI-MS, NMR, and ECD calculations. Compounds were evaluated for their anti-cardiomyocyte oxidative damage activity using a model of oxidative damage induced by cell hypoxia incubation. Muyocoxanthones O-Q and blennolide L exhibited moderate activity against oxidative damage to cardiomyocytes with relative viabilities of 62.4, 54.8, 60.3 and 54.9%, respectively. Graphical abstract: Xanthones isolated from an endophytic fungus Muyocopron laterale exhibited inhibitory activity against oxidative damage. Image 1 Highlights: Five undescribed xanthone analogues were isolated from an endophytic fungus Muyocopron laterale. The structures of the compounds were elucidated by spectroscopic methods. Four compounds exhibited inhibitory activity against oxidative damage to cardiomyocytes.